WAJAH MASJID DI MADURA (Studi Historis Dan Sosiologis Dinamika Manajemen Masjid dalam Pemberdayaan Ummat) - Nashar Nashar (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
The shifting paradigm about a mosque from not only as a central place to do worship becomes the central place to empower society needs to be spread out. Doing worship is not only by doing prayer for five times a day but also talking about how Moslems and society can rise up from the poverty. Here, the concept of  development becomes integrated  between the life and the hereafter. It makes the program of society’s empowerment through Posdaya created by the government under some institutions (PPKB, health, Damandiri, and others) need to be supported by all aspects of society. It also happens on the mind set changing of the mosque’s takmir about the function of the mosque. It changes from purely place to do worship to a center of society’s economic empowerment. Based on the background knowledge, the writer takes a tittle “the looks of mosques in Madura (historical and sosiological study on the mosque’s management dynamics in empowering society).